A biobjective production planning model and application of three LP procedures (1999)
A biobjective model is proposed for production planning in a multi-stage, multi-facility production system. The decision situation considered was a case where the Decision Maker (DM) wants to determine the quantities of materials to be fed into each production facility at each stage of production that gives maximal realization of his objectives. A numerical example is solved using three Linear Programming procedures. The methods used are: Compromise Constraint Biobjective LP (CCBLP), Linear Combination of the Objective Functions (LCOF) and Goal Programming (GP). The behaviour of the CCBLP model shows that it is superior to LCOF and non-preemptive GP in terms of its sensitivity to relaxations in the objectives. It also supports the result of an earlier research that the CCBLP gives the real compromise solution.